DNA Origami Post‐Processing by CRISPR‐Cas12a. Issue 10 (28th January 2020) - Xiong, Qiancheng; Xie, Chun; Zhang, Zhao; Liu, Longfei; Powell, John T; Shen, Qi; Lin, Chenxiang
Abstract: Customizable nanostructures built through the DNA‐origami technique hold tremendous promise in nanomaterial fabrication and biotechnology. Despite the cutting‐edge tools for DNA‐origami design and preparation, it remains challenging to separate structural components of an architecture built from—thus held together by—a continuous scaffold strand, which in turn limits the modularity and function of the DNA‐origami devices. To address this challenge, here we present an enzymatic method to clean up and reconfigure DNA‐origami structures. We target single‐stranded (ss) regions of DNA‐origami structures and remove them with CRISPR‐Cas12a, a hyper‐active ssDNA endonuclease without sequence specificity. We demonstrate the utility of this facile, selective post‐processing method on DNA structures with various geometrical and mechanical properties, realizing intricate structures and structural transformations that were previously difficult to engineer. Given the biocompatibility of Cas12a‐like enzymes, this versatile tool may be programmed in the future to operate functional nanodevices in cells. Abstract : Free at last : DNA‐origami nanostructures are set in motion by trans‐activated Cas12a that non‐specifically chips away single‐stranded loops, handles, and tension‐loaded tethers. This post‐assembly modification method greatly simplifies the design and fabrication of reconfigurable DNA structures, opening up opportunities to operate DNA nanodevices in cells.